Impact of Global Financial Crisis on Reserve Bank of India (RBI) as a National Regulator - Bhattacharya, Siddhartha; Sengupta, P. P.; Mishra, Rama Kant (Indian Journal of Finance, 2010)
The immediate result of tightening of the money and credit markets in October 2008 created demands on banks that were already expanding credit well beyond the resources raised from the public by way of deposits. Companies which were substituting overseas credit and capital market sources with bank funds started withdrawing funds parked with mutual funds and utilizing their undrawn limits with banks. Some of the companies that had issued commercial paper in the market- especially the real estate companies and the non banking companies found it difficult to roll over the maturing paper.The Commercial Paper and Certificates of Deposit markets became illiquid and mutual funds started facing severe redemption pressures.Hence, in the interest of maintaining financial stability, the RBI instituted a 14-day special repo facility for a notified amount of about 4 billion to alleviate liquidity stress faced by mutual funds, and banks were allowed temporary use of Statutory Liquidity Ratio (SLR) securities for collateral purposes for an additional 0.5 per cent of Net Demand and Time Liabilities exclusively for this. Subsequently, this facility was extended for Non Banking Finance Companies (NBFCs) and later to housing finance companies as well. The relaxation in the maintenance of the SLR was enhanced to the extent of up to 1.5 per cent of their NDTL. In order to curtail leveraging, commercial banks, all-India term lending and refinancing institutions were not allowed to lend against or buy back CDs held by mutual funds. This restriction was relaxed in the context of the drying up of liquidity for CDs and CPs. Considering the systemic importance of the NBFC sector, the Government, in consultation with the RBI announced the setting up of a special purpose vehicle (SPV) that could raise funds from the RBI against government-guaranteed bonds to meet the temporary liquidity.